Validitas Media Pembelajaran Interaktif Berbasis QR Code Terintegrasi Model Pembelajaran PBL pada Siswa SMP - A’yun, Siti Izatul; Murtini, Iin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The development of the times encourages various renewal efforts in the use of technology in the learning process. The purpose of this study is to design and test the validity of interactive learning media based on QR Code integrated with the Problem Based Learning (PBL) learning model for junior high school students. The research method used is the ADDIE development model which consists of five stages, namely analyze, design, development, implementation, and evaluate. The data collection technique is carried out through a product validation sheet filled out by five expert validators, consisting of three lecturers and two subject teachers. The validation results show that the material/content aspect obtained an average score of 84.61%, the systematic/graphics aspect was 81.42%, and the language aspect was 88%. The overall average of the three aspects reached 84.67%, which is categorized as very valid. In addition, the user-friendly aspect obtained an average score of 85.3%, while the ease of use aspect reached 93.8%, with a combined average of 89.55%. These findings indicate that QR Code-based interactive learning media is feasible and can be an innovative alternative to support active problem-based learning at the junior high school level.